2010
DOI: 10.1029/2009wr008756
|View full text |Cite
|
Sign up to set email alerts
|

Two‐zone transient storage modeling using temperature and solute data with multiobjective calibration: 1. Temperature

Abstract: [1] This paper presents the formulation and calibration of the temperature portion of a two-zone temperature and solute (TZTS) model which separates transient storage into surface (STS) and subsurface transient storage (HTS) zones. The inclusion of temperature required the TZTS model formulation to differ somewhat from past transient storage models in order to accommodate terms associated with heat transfer. These include surface heat fluxes in the main channel (MC) and STS, heat and mass exchange between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(99 citation statements)
references
References 37 publications
5
94
0
Order By: Relevance
“…It should also be noted that this calibration does not capture the peak of the tracer at Site 3, nor the tail of the tracer curve at Site 2, which is critical to understanding the transient storage within the study reach (Bencala and Walters, 1983). Similar to what Neilson et al (2010a) found, comparing Level 1 and 2 results (Table 3) illustrates the relative benefit of using two-objective optimization compared to single-objective optimizations. For Tests 5-10, Tests 6 and 10 did not meet the local criteria of E > 0.8 with tracer data used as a calibration objective, although Test 6 did meet the global criteria (Table 3).…”
Section: Levelsupporting
confidence: 73%
See 4 more Smart Citations
“…It should also be noted that this calibration does not capture the peak of the tracer at Site 3, nor the tail of the tracer curve at Site 2, which is critical to understanding the transient storage within the study reach (Bencala and Walters, 1983). Similar to what Neilson et al (2010a) found, comparing Level 1 and 2 results (Table 3) illustrates the relative benefit of using two-objective optimization compared to single-objective optimizations. For Tests 5-10, Tests 6 and 10 did not meet the local criteria of E > 0.8 with tracer data used as a calibration objective, although Test 6 did meet the global criteria (Table 3).…”
Section: Levelsupporting
confidence: 73%
“…The E values reported for the two-objective optimizations are based on the parameter set that represents the best trade-off solution or the pareto solution (Vrugt et al, 2003a,b;Boyle et al, 2000;Gupta et al, 1998Gupta et al, , 2003Neilson et al, 2010a). The best results are from Test 7 with values of 7 E MC2,Tr = 0.94, 7 E MC2,Temp = 0.91, and AE s = 0.81 (Table 3).…”
Section: Levelmentioning
confidence: 78%
See 3 more Smart Citations